2D tungsten nanosheets: ascendant nonlinear absorption properties in the ultraviolet band. Issue 17 (7th April 2022) - Yuan, Junjie; Xin, Yi; Wang, Xinyu; Liu, Yiping; Zhao, Zhenyu; Du, Binjian; Xing, Fei; Zhang, Fang
Abstract : The NLA properties of 2D tungsten nanosheets were explored by the open aperture Z-scan technique. The results demonstrated their excellent NLA values in the ultraviolet band, which could draw people's attention to transition metal elements. Abstract : Tungsten, a group VIB transition metal with an atomic number of 74, has been continuously excavated and studied to further its applications in the industrial and military fields. However, research on the nonlinear optical properties of the transition metal tungsten is rare, which gives us new research impetus. Hence, in this work, the nonlinear optical properties of 2D tungsten nanosheets (fabricated by the LPE method) were explored by employing the open aperture Z-scan technique with broadband wavelengths for the first time to the best of our knowledge. The results demonstrate that 2D tungsten nanosheets possess excellent nonlinear optical values in the ultraviolet band. Our research is of great significance in strengthening the nonlinear optical applications of tungsten and inspiring people to dig deeper into transition metal elements.